Systematic Literature Review (SLR) : Penggunaan Media Pembelajaran Matematika Berbasis Aplikasi Scratch - Aulia Herdiyanti; Yahfizham Yahfizham (Student Scientific Creativity Journal, 2024)
Along with the development of technology, application/software-based learning media is needed to help students understand mathematics material. This study aims to identify, review, and conclude related to the use of scratch application-based math learning media. The method used is Systematic Literature Review (SLR). Using the Google Scholar database, articles were searched according to the topics studied in the 2019-2024 time span. The search was based on Garuda and Sinta 1-6. The results showed that the use of mathematics learning media based on scratch application optimizes students' problem solving and improves students' understanding of mathematics concepts, thus increasing their involvement and making learning more fun.